Testify - Manuel, Doug (Book collections on Project MUSE., 2017)
This award-winning debut book of poetry examines race, masculinity, religion, class, and the African American experience in the American Midwest.A book of elegiac ambivalence, Testify's speaker often finds himself trapped between received binaries: black and white, ghetto and suburban, atheism and Catholicism. In many ways, this work is a Bildungsroman detailing the maturation of a black man raised in the crack-laden 1980s, with hip-hop, jazz, and blues as its soundtrack. Rendered with keen attention to the economic decline of the Midwest due to the departure of the automotive industry, this book portrays the speaker wrestling with his city's demise, family relationships, interracial love, and notions of black masculinity. Never letting anyone, including the speaker, off the hook, Testify refuses sentimentality and didacticism and dwells in a space of uncertainty, where meaning and identity are messy, complicated, and multivalent."Manuel charts the raw emotional complexities and the impossible daily reckonings that confront a young black man coming of age today in America. . . . Each powerful testimony in this collection stands as evidence of an eloquent and dramatic new voice in American poetry." --David St. John, author of The Auroras and Study for the World's Body "These potent poems testify to those ambivalent moments that might rend or right us, as when an interracial couple drive past a truck with a Confederate flag painted on its back windshield and from which a little boy turns to smile and wave: his 'blond hair // split down the middle like a Bible / left open to the Book of Psalms.'" --Anna Journey, author of The Atheist Wore Goat Silk